Burden of Surgical Treatment for the Management of Cervical Myelopathy in Mucopolysaccharidoses: A Systematic Review - Roberta Costanzo; Lapo Bonosi; Massimiliano Porzio; Federica Paolini; Lara Brunasso; Andrea Evier Giovannini; Manikon Poullay Silven; Giuseppe Roberto Giammalva; Giuseppe Emmanuele Umana; Gianluca Scalia; Domenico Gerardo Iacopino; Rosario Maugeri (Brain Sciences, 2022)
Mucopolysaccharidoses (MPSs) are a rare group of heterogeneous genetic and metabolic disorders, caused by loss of functions of several enzymes that are involved in glycosaminoglycan catabolism. Their progressive accumulations in cells, tissues, and consequently, organs lead to several clinical manifestations, such as musculoskeletal involvement. Indeed, the most common manifestation in the central nervous system is represented by cervical spinal stenosis due to bony alterations or dural thickening. Cervical involvement can commonly cause myelopathy and instability exerting severe symptoms. A prompt diagnosis and treatment of the aforementioned conditions is mandatory to ensure a better quality of life in patients with such debilitating disorders. Nevertheless, a clear consensus about their management (i.e., surgical or not) is still lacking, leading to an inevitable delay. This review aims to investigate and discuss the main causes of myelopathy in patients with mucopolysaccharidoses, available therapeutic strategies, and the impact and role of surgery on the neurological outcome.